An integrated view of p53 dynamics, function, and reactivation. (April 2021) - Demir, Özlem; Barros, Emilia P; Offutt, Tavina L; Rosenfeld, Mia; Amaro, Rommie E
Highlights: P53 consists of distinct domains that have typically been studied in isolation. However, studies highlight concerted dynamics and regulation between the domains. Computational methods are now able to model and study multi-domain proteins. P53 represents a case study for investigating IDPs and new therapeutic modalities. Abstract : The tumor suppressor p53 plays a vital role in responding to cell stressors such as DNA damage, hypoxia, and tumor formation by inducing cell-cycle arrest, senescence, or apoptosis. Expression level alterations and mutational frequency implicates p53 in most human cancers. In this review, we show how both computational and experimental methods have been used to provide an integrated view of p53 dynamics, function, and reactivation potential. We argue that p53 serves as an exceptional case study for developing methods in modeling intrinsically disordered proteins. We describe how these methods can be leveraged to improve p53 reactivation molecule design and other novel therapeutic modalities, such as PROteolysis TARgeting Chimeras (PROTACs).